PENERAPAN TOTAL QUALITY MANAGEMENT (TQM) DALAM MENCAPAI KEPUASAN SISWA - Alfaiz, Baraz Yoechva (Program Studi Pendidikan Islam Pascasarjana UIN Sumatera Utara Medan, 2025)
Abstract: Total Quality Management (TQM) is a management concept of educational institutions oriented towards improving quality through a continuous improvement process, focusing on customer satisfaction, and full involvement of all elements of the organization. Implementing TQM in the context of education involves harmonious collaboration between various internal components, such as principals, teachers, and staff, as well as the support of external parties, including school committees. This collaboration aims to provide optimal service to students as the main customer. This study aims to describe and analyze the implementation of TQM carried out by school principals, teachers, and school committees to achieve student satisfaction. This research uses a qualitative approach with data collection methods in the form of interviews, observations, and documentation. The results of the study show that SMAN 1 Rogojampi adopts TQM by integrating the visionary leadership of the principal, the active contribution of teachers, and the strategic support of the school committee. The implementation of TQM at SMAN 1 Rogojampi is guided by the ISO 9001:2008 quality standard, which is a reference to achieve customer satisfaction effectively and sustainably.Keywords: Total Quality Management (TQM), the principal teacher's School Committee, student satisfaction.Abstrak Total Quality Management (TQM) adalah sebuah konsep pengelolaan lembaga pendidikan yang berorientasi pada peningkatan kualitas melalui proses perbaikan berkesinambungan, fokus terhadap kepuasan pelanggan, dan keterlibatan penuh seluruh elemen organisasi. Implementasi TQM dalam konteks pendidikan melibatkan kolaborasi harmonis antara berbagai komponen internal, seperti kepala sekolah, guru, dan staf, serta dukungan pihak eksternal, termasuk komite sekolah. Kerja sama ini bertujuan untuk memberikan pelayanan yang optimal kepada siswa sebagai pelanggan utama. Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis penerapan TQM yang dilakukan oleh kepala sekolah, guru, dan komite sekolah dalam upaya mencapai kepuasan siswa. Penelitian ini menggunakan pendekatan kualitatif dengan metode pengumpulan data berupa wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa SMAN 1 Rogojampi mengadopsi TQM dengan mengintegrasikan kepemimpinan visioner kepala sekolah, kontribusi aktif dari guru, serta dukungan strategis dari komite sekolah. Implementasi TQM di SMAN 1 Rogojampi berpedoman pada standar mutu ISO 9001:2008, yang menjadi acuan dalam upaya mencapai kepuasan pelanggan secara efektif dan berkelanjutan.Kata Kunci: Total Quality Management (TQM), Komite Sekolah, Kepuasan Siswa